The Evolution of Innovative Financial Instruments in India’s Securities Market: Trends and Investor Dynamics - Guduri Nagaveni, Dr N Subrahmanyam, D. Satish Babu, Dr. Ankireddy Yenireddy (South Eastern European Journal of Public Health, 2025)
Indian securities market has witnessed tremendous changes over the last decade, with such changes having been driven both by regulatory reforms and the development of innovative financial instruments. The paper explores dynamic changes in the market brought about by various regulatory interventions, technological advancements, and innovative instruments that have broadened the investor base and strengthened market integrity. Apart from setting up Social Stock Exchange, important innovation products such as green bonds, REITs, and InvITs are brought under scrutiny to find out their impact on investor interest and the way to achieve good performance. The research would aim to enlighten stakeholders, ranging from regulatory authorities to global investors, on trends related to India's securities market changing structure towards investment destination potential.